2021
DOI: 10.1101/2021.01.07.425766
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nectar bacteria stimulate pollen germination and bursting to enhance their fitness

Abstract: For many flower visitors, pollen is the primary source of non-carbon nutrition, but pollen has physical defenses that make it difficult for consumers to access nutrients. Nectar-dwelling microbes are nearly ubiquitous among flowers and can reach high densities, despite the fact that floral nectar is nitrogen limited, containing only very low concentrations of non-carbon nutrients. Pollen contains trace micronutrients and high protein content but is protected by a recalcitrant outer shell. Here, we report that … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 63 publications
(94 reference statements)
1
8
0
Order By: Relevance
“…This study provides evidence that even when pollen grains remain intact, pollen can provide amino acids to nectar and improve microbial growth. Furthermore, because M. reukaufii inoculation did not result in obvious damage to pollen as has been reported for other nectar microorganisms (Christensen et al, 2021), it may be that this yeast has limited negative impacts on plant reproduction and particularly male fitness, as has been reported previously (Schaeffer and Irwin, 2014;Yang et al, 2019; but see Herrera et al, 2013). Our results also suggest a previously overlooked and important role of pollen in nectar sugar concentrations, decreasing sucrose via its conversion to glucose and fructose.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This study provides evidence that even when pollen grains remain intact, pollen can provide amino acids to nectar and improve microbial growth. Furthermore, because M. reukaufii inoculation did not result in obvious damage to pollen as has been reported for other nectar microorganisms (Christensen et al, 2021), it may be that this yeast has limited negative impacts on plant reproduction and particularly male fitness, as has been reported previously (Schaeffer and Irwin, 2014;Yang et al, 2019; but see Herrera et al, 2013). Our results also suggest a previously overlooked and important role of pollen in nectar sugar concentrations, decreasing sucrose via its conversion to glucose and fructose.…”
Section: Discussionsupporting
confidence: 83%
“…Because nectar contains high sugar concentrations and a paucity of amino acids and proteins, pollen has been hypothesized to provide a key source of nitrogen to nectar‐inhabiting microorganisms. Microbes have been observed clustering around and sometimes rupturing pollen grains (Herrera, 2017) and recent studies have confirmed that pollen increases the population density of nectar‐inhabiting microbes (Pozo and Jacquemyn, 2019; Christensen et al ., 2021). Some Acinetobacter species trigger pollen germination, thereby improving access to pollen nutrients (Christensen et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, bacteria and/or fungi dominant on old flowers might have indirectly decreased fruit set by changing the microenvironment of flowers. Some flower microbes are known to inhibit pollen germination or pollen tube growth (Christensen et al 2021; Eisikowitch et al 1990), while the effects of microbes on other post-pollination processes are largely understudied (Cullen et al 2021). On the other hand, it is unlikely that pollinator behavioral response affected the fruit set as reported in previous studies (Sobhy et al 2018; Vannette et al 2013), because we hand-pollinated the flowers under the fruit set monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Nectar yeasts are reported to modify pollinator foraging patterns and reduce pollination success (Herrera et al 2013). Acinetobacter bacteria that commonly inhabit floral nectar exploit pollen nutrition by inducing pollen germination and bursting (Christensen et al 2021). Most studies of these phenomena examined the effects of an individual microbial species or of separate strains rather than that of the whole community.…”
Section: Introductionmentioning
confidence: 99%